The Copy Cat Disease: A Case of Lupus Podocytopathy - Joshi, Rina; Mansoor, Maryah (British Journal of Healthcare and Medical Research, 2022)
Systemic Lupus Erythematosus (SLE) is a chronic inflammatory disease that can affect various organs. Specifically, when the kidneys are affected this can result in nephritic or nephrotic syndrome. Lupus podocytopathy (LP) is a type of nephrotic syndrome associated with SLE. This case looks at a 44 year old female who presented to the emergency department (ED) with bilateral lower extremity edema and was noted to have hypoalbuminemia and an elevated total protein/creatinine ratio. She was discharged from the ED with a diagnosis of nephrotic syndrome and advised to follow up with nephrology as an outpatient. Her outpatient labs were positive for antinuclear antibodies (ANA), anti-ribonucleoprotein antibodies (anti-RNP), and anti-smith antibodies. She returned to the ED two weeks later for hand cramping and was admitted for an acute kidney injury. She had an inpatient renal biopsy performed which showed 100% podocyte effacement, concerning for minimal change disease (MCD). However, the biopsy also showed a positive tissue ANA with no immune complex deposition. In the context of MCD and a positive tissue ANA, this patient was diagnosed with LP. She was treated with steroids and hydroxychloroquine with improvement in her kidney function and proteinuria. Lupus podocytopathy is a new entity that is not classified in the 2018 International Society of Nephrology/Renal pathology Society (ISN/RPS) classification system [1]. It is treated similarly to MCD, with steroids and possibly immunosuppressive agents. Clinicians should keep autoimmune conditions on their differential when evaluating and treating patients with nephrotic syndrome.